Влияние газонасыщенности на процессы трещинообразования и разрушения горных пород - Макеев, С.Ю.; Осенний, В.Я.; Дякун, Р.А. (Геотехническая механика, 2012)
Наведені результати експериментальних досліджень щодо навантаження зразків гірничих
порід різного ступеню газонасиченгості. Встановлено, що границя міцності на одновісне
стиснення дегазованих зразків алевроліта кубічної форми в середньому у 1,3 рази більше,
ніж у газонасичених, а питома енергія, яка передана дегазованими зразками перед їх
руйнуванням, у 1,5 рази перевищує енергію зразків, насичених газом. Results of experimental researches are brought on the loading of rock samples with different
degree of satiation gas. It is set that tensile strength on the monaxonic compression of gas-free rock samples of cube form siltstone on the average there is more in 1,3 time, than at saturated by gas, and the specific energy transmitted to gas-free rock samples before their destruction, in 1,5 time exceeds energy of the rock samples saturated by gas.